2005
DOI: 10.1021/cg050219v
|View full text |Cite
|
Sign up to set email alerts
|

Single-Crystal, Polarized Raman-Scattering Study of the Molecular and Lattice Vibrations for the Energetic Material Cyclotetramethylenetetranitramine, β-Polymorph (β-HMX)

Abstract: The single-crystal polarized Raman spectra for cyclotetramethylenetetranitramine, -polymorph ( -HMX), are reported over the region of 10 to 3150 cm -1 . While the agreement with previous Raman studies is quite good, a consistent interpretation of the Raman spectra is provided through assignment of fundamental modes, overtones, and combination bands. This affords the first assignment of all six Raman-active optical phonons of -HMX. It was found that three A g symmetry librations are accidentally degenerate with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…A later investigation by Palmer et al [24] into the general mechanical properties of β-HMX embedded as a plastic bonded explosive has also been reported, and a detailed examination in part of the present study [25] has shown by etching methods that growth dislocations emergent on the (010) face are of either edge (∣ b ∣ = [010]) or screw (∣ b ∣ = [010]) type. Better understanding of the contribution of phonons and lattice vibrations to detonation via elastic properties have been made experimentally [26,27] and with supporting computational studies [28,29]. In addition a nanoindentation study [30] has indicated that the hardness of the (010) face of β-HMX is ~1080 MPa, which is much higher than that found in previous studies.…”
Section: Introductionmentioning
confidence: 92%
“…A later investigation by Palmer et al [24] into the general mechanical properties of β-HMX embedded as a plastic bonded explosive has also been reported, and a detailed examination in part of the present study [25] has shown by etching methods that growth dislocations emergent on the (010) face are of either edge (∣ b ∣ = [010]) or screw (∣ b ∣ = [010]) type. Better understanding of the contribution of phonons and lattice vibrations to detonation via elastic properties have been made experimentally [26,27] and with supporting computational studies [28,29]. In addition a nanoindentation study [30] has indicated that the hardness of the (010) face of β-HMX is ~1080 MPa, which is much higher than that found in previous studies.…”
Section: Introductionmentioning
confidence: 92%
“…[55] The shoulder at 173 cm −1 is assigned to the COO − torsion mode and is an intramolecular fundamental lattice vibration, which can be in Fermi resonance with the first overtone of the 61 cm −1 fundamental optical phonon. [56] The vibration centred at approximately at 140 cm −1 as a result of the deformation and torsional motion of the methyl group is also a fundamental lattice vibration. [55 -58] The 90 cm −1 Raman band cannot be used to provide any overtone or combination modes.…”
Section: N Peicamentioning
confidence: 99%
“…3d). [27,47,56,66] In the Raman spectra in the acidic pH range 2-0 (Fig. S3, Table S3 in Supporting Information), new bands appear in the low wavenumber region (700-200 cm −1 ) and are attributed to the carboxylate bending mode (pH 1, 650 cm −1 ), [32] phenylalanine and Amide IV vibrations (pH 1, 624 cm −1 ), [42] Amide VI and C1OO − wagging mode (pH 1, 601 cm −1 ), [32,42] N-C O bending mode and primary saturated aliphatic amides (pH 1, 581 cm −1 ), [67] COO − bending mode (pH 1, 524, 333 cm −1 ), [32,67] ring out-ofplane bending mode (pH 1, 478 cm −1 ).…”
Section: Ph Dependence Raman Spectra Of E951mentioning
confidence: 99%
“…In two previous Raman scattering studies of ␤-HMX, an energetic material similar to RDX, an occurrence of accidentally degenerate optical phonons was reported. 14,25 To be assured that these are accidental degeneracies of RDX, the possibility of breakthrough scattering must be considered. Breakthrough scattering has been used as an explanation of the appearance of disparate symmetries in a given vibrational spectrum.…”
Section: Lattice Modesmentioning
confidence: 99%